Endovascular revascularization vs. open surgical revascularization for patients with lower extremity artery disease: a systematic review and meta-analysis - Shu, Hongxin; Xiong, Xiaowei; Chen, Xiaomei; Sun, Xiaolei; Zhang, Rong; Wang, Ruihua; Huang, Qun; Zhu, Jun (Frontiers in Cardiovascular Medicine, 2023)
Background: Currently, the main treatment for lower extremity artery disease (LEAD) is revascularization, including endovascular revascularization (EVR) and open surgical revascularization (OSR), but the specific revascularization strategy for LEAD is controversial. This review provided the comprehensive and recent evidence for the treatment of LEAD. Methods: Medline, Embase, and the Cochrane Library databases were searched for relevant articles. Randomized controlled trials (RCTs) and cohort studies comparing the short-term or long-term outcomes between EVR and OSR of LEAD were identified. Short-term outcomes were 30-day mortality, major amputation, wound complication, major adverse cardiovascular events (MACEs), and length of hospital stay (LOS), while long-term outcomes included overall survival (OS), amputation-free survival (AFS), freedom from re-intervention (FFR), primary patency (PP), and secondary patency (SP). Results: 11 RCTs and 105 cohorts involving 750134 patients were included in this analysis. For the pooled results of cohort studies, EVR markedly decreased the risk of 30-day mortality, wound complication, MACEs, LOS, but increased the risk of OS, FFR, PP, and SP. For the pooled outcomes of RCTs, EVR was associated with obviously lower 30-day mortality, less wound complication and shorter LOS, but higher risk of PP, and SP. However, both RCTs and cohorts did not show obvious difference in 30-day major amputation and AFS. Conclusions: Both the pooled results of cohorts and RCTs indicated that EVR was associated with a lower short-term risk for LEAD, while OSR was accompanied by a substantially lower long-term risk. Therefore, the life expectancy of LEAD should be strictly considered when choosing the revascularization modality. As the current findings mainly based on data of retrospective cohort studies, additional high-quality studies are essential to substantiate these results.